Exploring Correlates of Student Preferences for Virtual or In-Class Learning among Neurodiverse Adolescents Using a Single-Case Design Methodology - Taryn A. Myers; John D. Ball; Mindy Gumpert; Mary Roberts (MDPI AG, 2023)
The purpose of the current study is to explore several correlates of adolescent students' preferences for at-home virtual or in-class in-person learning in a single case of a school that serves students with learning differences. Correlates of interest were the Big Five personality traits (Openness to Experience, Conscientiousness, Extroversion, Agreeableness, Neuroticism) and the students' self-reported learning engagement. Participants were recruited from a single independent school for students with neurodiversity and special learning needs, where they had high exposure to computer-/internet-assisted learning. Twenty-seven students responded to questionnaires measuring preferred learning modes, personality traits, and learning engagement. Despite teacher reports that some of these students thrived with virtual learning during the COVID-19 pandemic, 88.5% of this sample preferred in-class learning. The personality traits of Conscientiousness and Openness to Experience were related to a preference for in-class learning. A preference for in-class learning was related, in turn, to learning engagement. Learning engagement was associated with Conscientiousness, Agreeableness, and lower levels of Neuroticism. The strengths and limitations of this study and its implications for further research and practice are discussed.